Pengaruh Current Ratio, Debt Ratio, Net Profit Margin Dan Return On Equity Terhadap Financial Distress - Dwi Fitrianingsih; Luly Novitasari (AKUNTANSI DEWANTARA, 2021)
This study aims to find out "Financial Ratios to Predict the Condition of Financial Distress in Manufacturing Companies Listed on the Stock Exchange" with a total sample of 42 manufacturing companies listed on the Indonesia Stock Exchange. Data collection techniques used purposive sampling and the number of samples in this research is 42 data.From the results of the partial test (t test) that the Current Ratio (CR) variable has a positive effect on Financial Distress, Debt Ratio (DR) has a positive effect on Financial Distress, Net Profit Margin (NPM) has a positive effect on Financial Distress, Return On Equity (ROE) does not affect the Financial Distress. As well as simultaneous testing (test f) Current Ratio (CR), Debt Ratio (DR), Net Profit Margin (NPM), Return On Equity (ROE) simultaneously have a positive effect on Financial Distress.